Interlinkages and gaps: a review of the literature on intergovernmental relations for flood management in the face of climate change - Chantilas, Alexander; El-Khattabi, Ahmed Rachid; Gvino, Emily; Downs, Kristen; Byrne, Cate; Christenson-Diver, Elizabeth; Ruffins, Ranger; Worley, Aaron; Dodds, Felix (Frontiers in Sustainable Cities, 2023)
Current approaches to flood management are increasingly insufficient to deal with intensifying flood trends. In this paper, we define and map out the responsibilities and relationships of local, state, and federal governing entities at various levels. We use these relationships to identify gaps in governance needed to address the high financial, human, and infrastructure costs of flooding. This paper offers a description of current flood policies and provides recommendations for innovations in policy solutions to improve governance gaps. We identify three themes from the literature on intergovernmental relations and flood governance: (1) intergovernmental relations (interlinkages and gaps) for flood governance; (2) risks inherent to flood governance (financial, physical, social and individual, and perception of risk); (3) data adequacy and interoperability.